Pengaruh Fraud Diamond dan Penyalahgunaan Teknologi Informasi Terhadap Perilaku Kecurangan Akademik Pada Siswa Kelas XI di SMAN 11 Semarang - Baihaqi Rizqi Fajarwati; Ahmad Nurkhin (Journal of Accounting, Economics, and Business Education, 2025)
The purpose of this study was to analyze and examine the effect of Fraud Diamond (pressure, opportunity, rationalization, and ability) and misuse of information technology on academic fraud behavior in class XI students at SMAN 11 Semarang. The population of this study were all the students of Class XI. The study used a cluster random sampling technique with 216 respondents. Data collection method using questionnaire. Data analysis using descriptive statistical analysis and path analysis with the help of analytical tools in the form of Excel and Smart-PLS 4. The results of this study indicate that opportunity, rationalization and ability have a positive effect on academic cheating behavior in grade XI students at SMAN 11 Semarang. Pressure and misuse of information technology have no effect on academic cheating behavior in class XI students at SMAN 11 Semarang. The suggestion of this research is that schools need to increase students' moral awareness and honesty through integration in the learning process. Schools can apply educational sanctions that have a positive impact on students who commit fraud, and teachers can evaluate the learning process on the achievement of students. Future research is expected to abuse information technology as a moderating variable and add self- control as an independent variable that can affect academic cheating behavior